MENSTRUAL CYCLE AND THE INCIDENT OF ANEMIA IN TEENAGE WOMEN - Putri, Tsalsa; Nuraeni, Neni; Nurlina, Fitri (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2023)
The prevalence of anaemia in Indonesia is still high, especially in adolescent girls. This is due to nutritional status, stress levels, knowledge and menstrual disorders. Menstrual disorders are related to the cycle or duration of menstruation or the amount of blood that comes out. The impact that occurs adolescents will feel weak, tired, lethargic, difficult to concentrate and for the long term related to fertility, and there is a possibility to deliver baby with weight and premature birth. The purpose of the study was to determine the relationship between the menstrual cycle and the incidence of anaemia in adolescent girls. Correlational descriptive research method with cross sectional approach. The sample was 68 respondents with total sampling. Data were collected through questionnaires in the form of fill-in sheets for menstrual cycles and anemia using easy touch to determine Hb levels. The results showed that respondents who experienced a normal cycle as many as 41 respondents (60.3%), 16 respondents (23.5%) experienced a long cycle and as many as 11 respondents (16.2%) experienced a short cycle. Respondents who experienced anemia as many as 36 respondents (52.9%) and did not have anemia as many as 32 respondents (47.1%). The results of the statistical test obtained a ρ value of 0.000. The conclusion of this study is that there is a relationship between the menstrual cycle and the incidence of anemia in adolescent girls. It is recommended for the nursing profession to provide information through health counseling in collaboration with the community and schools about anemia and its causative factors to improve the health status of adolescent girls